Characterization of Zinc Carbonate Basic as a Source of Zinc in a Rodent Study Investigating the Effects of Dietary Deficiency or Excess. (13th October 2017) - Levine, Keith E.; Collins, Bradley J.; Stout, Matthew D.; Wyde, Michael; Afton, Scott E.; Essader, Amal S.; Ennis, Todd J.; Amato, Kelly E.; McWilliams, Andrea C.; Fletcher, Brenda L.; Fernando, Reshan A.; Harrington, James M.; et al.
ABSTRACT: Zinc deficiency and excess can result in adverse health outcomes. There is conflicting evidence regarding whether excess or deficient zinc in the diet can contribute to carcinogenicity. The objective of this study was to characterize zinc carbonate basic for use as a source of dietary zinc in a rodent toxicity and carcinogenicity study investigating the effects of zinc deficiency and excess. Because of the complex chemistries of zinc carbonate basic compounds, inconsistent nomenclature, and literature and reference spectra gaps, it was necessary to use multiple analytical techniques, including Karl Fischer titration, combustion analysis, inductively coupled plasma–optical emission spectrometry, X-ray diffraction, infrared spectroscopy, X-ray fluorescence spectrometry, and thermogravimetric analysis to characterize the test article. Based on the collective evidence and through the process of elimination, the test article was found to be composed mainly of zinc carbonate basic with zinc oxide as a minor component. The zinc content was determined to be 56.6% (w/w) with heavy metals such as arsenic, cadmium, mercury, and lead below the limit of quantitation of less than or equal to 0.01%. The test material was stable at ambient temperature. Based on the work described in this manuscript, the test article was suitable for use as a source of zinc in studies of deficiency and excess in the diet.